Expression of placental CD146 is dysregulated by prenatal alcohol exposure and contributes in cortical vasculature development and positioning of vessel-associated oligodendrocytes - Sautreuil, Camille; Lecointre, Maryline; Dalmasso, Jessica; Lebon, Alexis; Leuillier, Matthieu; Janin, François; Lecuyer, Matthieu; Bekri, Soumeya; Marret, Stéphane; Laquerrière, Annie; Brasse-Lagnel, Carole; Gil, Sophie; et al. (Frontiers in Cellular Neuroscience, 2024)
Recent data showed that prenatal alcohol exposure (PAE) impairs the "placenta-brain" axis controlling foetal brain angiogenesis in human and preclinical models. Placental growth factor (PlGF) has been identified as a proangiogenic messenger between these two organs. CD146, a partner of the VEGFR-1/2 signalosome, is involved in placental angiogenesis and exists as a soluble circulating form. The aim of the present study was to investigate whether placental CD146 may contribute to brain vascular defects described in foetal alcohol spectrum disorder. At a physiological level, qRT-PCR experiments performed in human placenta showed that CD146 is expressed in developing villi and that membrane and soluble forms of CD146 are differentially expressed from the first trimester to term. In the mouse placenta, a similar expression pattern of CD146 was found. CD146 immunoreactivity was detected in the labyrinth zone and colocalized with CD31-positive endothelial cells. Significant amounts of soluble CD146 were quantified by ELISA in foetal blood, and the levels decreased after birth. In the foetal brain, the membrane form of CD146 was the majority and colocalized with microvessels. At a pathophysiological level, PAE induced marked dysregulation of CD146 expression. The soluble form of CD146 decreased in both placenta and foetal blood, whereas it increased in the foetal brain. Similarly, the expression of several members of the CD146 signalosome, such as VEGFR2 and PSEN, was differentially impaired between the two organs by PAE. At a functional level, targeted repression of placental CD146 by in utero electroporation (IUE) of CRISPR/Cas9 lentiviral plasmids resulted in i) a decrease in cortical vessel density, ii) a loss of radial vascular organization and iii) a reduced density of oligodendrocytes. Statistical analysis showed that the more the vasculature was impaired, the more the cortical oligodendrocyte density was reduced. Altogether, these data support that placental CD146 contributes to the proangiogenic "placenta-brain" axis and that placental CD146 dysfunction contributes to the cortical oligo-vascular development. Soluble CD146 would represent a promising placental biomarker candidate representative of alcoholinduced neurovascular defects in neonates, as recently suggested by PlGF (patents WO2016207253 and WO2018100143).